A review: How does air quality feedback benefit the implementation of smoke-free homes initiative? - Sadewa, Deskantari Murti Ari; Bintoro, Bagas Suryo (Journal of Community Empowerment for Health, 2025)
Introduction: Smoke-free regulations forbidding smoking in all indoor settings are perceived as effective. In Indonesia, 59,3% of adults were exposed to SHS from in-house smoking.  Smoke-Free Homes (SFH) programs can potentially improve health outcomes and encourage smoke-free environments, but some challenges remain to be addressed.  Air quality feedback can be used as an additional tool that provides objective information on how smoking affects the amounts of air pollutants in their home as a promising technique to promote behavior change. This study aims to explore the usage of air quality feedback on the implementation of SFH.Methods: A comprehensive literature review on PubMed entered from 2008-2024 was undertaken with the keywords “air quality AND feedback AND smoke-free”.Results: In total, the search identified 10 articles that met the inclusion criteria. Most of the constructs in the articles had similarities, so findings were abstracted into a table according to intervention, device, place-to-device installments, feedback delivery, measurement, duration, and outcome. Most of the study was conducted in high-income countries. SHS-related PM2.5 concentration was detected at home with ‘Dylos’ in the majority of the studies. The household was provided personalized information on the PM2.5 concentration using various media, including modern technology. The findings of this study showed varied results on the PM2.5 concentration. However, different strategies were needed in some disadvantaged and vulnerable populations to promote behavior change.Conclusion: This study depicts the role of air quality feedback in supporting the implementation of SFH initiatives. The implementation of indoor air quality feedback has shown varying degrees of results in improving indoor quality. Nonetheless, it is thought that air quality feedback is an affordable, practical, and accessible intervention that can be used in Low-Middle Income Countries (LMICs) to supplement the SFH initiatives